THE ACCURACY OF EARNINGS FORECAST AND POST-IPO EARNINGS MANAGEMENT - Hutagaol, Yanthi; Warganegara, Dezie L.; Wibisono, Christofer (Jurnal Keuangan dan Perbankan, 2012)
Prior studies showed that before IPO, many companies conducted earnings management in order to attract potential investors through impressive earnings figures. This study aimed to investigate the tendency of earningsmanagement practice post - IPO. This practice of earnings management was motivated to preserve managers’reputation in achieving their earnings forecasts. Using a total of 165 IPOs in IDX during year 2000-2010, thisstudy employed descriptive analyses to identify the earnings management differences within the sample. A crosssectionanalysis was conducted to test the difference of earnings management indicator among the forecasters.Then, controlling for audit quality, ownership, firm size, and firm leverage, a regression analysis was performedto test the impact of earnings forecasts accuracy on the earnings management. The result of this research showedthat there was an indication that the forecasters conducted more earnings management than the non-forecasters.The study found that forecast accuracy was significantly related to managers’ behavior to manage post-IPOearnings. Further analysis showed that optimistic forecasters tended to engage more in more earning managementthan conservative forecasters. The cross section analysis confirmed that optimistic earnings forecast strengthenedthe relationship of forecast accuracy and post-IPO earnings management, while high audit quality failed toweaken it.